Advising the Management: A Theory of Shareholder Engagement - Kakhbod, Ali; Loginova, Uliana; Malenko, Andrey; Malenko, Nadya (Review of Financial Studies, 2023)
We study the effectiveness of shareholder engagement, that is, shareholders communicating their views to management. When shareholders and management have different beliefs, each shareholder engages more effectively when other shareholders engage as well. A limited shareholder base can thus prevent effective engagement. However, a limited shareholder base naturally arises under heterogeneous beliefs because investors who most disagree with management do not become shareholders. Passive funds, which own the firm regardless of their beliefs, can counteract these effects and improve engagement. When shareholders’ and management’s preferences are strongly misaligned, shareholders’ engagement decisions become substitutes and the role of ownership structure declines. Authors have furnished an Internet Appendix, which is available on the Oxford University Press Web site next to the link to the final published paper online.